Geopolitical factors of the new silk road construction - Аубакирова, А. А. (Journal of Oriental Studies, 2018)
The purpose of the research is to show the influence of Kazakhstan’s geopolitical factors in participating in the Chinese project «The Economic Belt of the New Silk Road.» The methodology of the research covers general scientific principles of cognition of economic and political phenomena – dialectical, concrete historical, systemic, which allow us to consider the interests of Kazakhstan and countries along the New Silk Road, as well as the risks arising in the course of construction. Traditional methods were also used, such as comparative, economic and statistical analysis and synthesis. Originality / value – the political and geographical position of Kazakhstan in the center of Eurasia continent between China, Russia and Europe is considered in historical aspect; the change in the economic and political situation of Kazakhstan in recent times in connection with the strengthening of China as the second economy of the world, the joint steps on the formation of China’s «One Belt-One Way» initiative and the «Nurly Zhol» Kazakhstan program were considered. Conclusion – as a result of the conducted research it was revealed that against the backdrop of China’s great successes in the world economy and its transformation into a major economic and political actor not only in Eurasia but also in the world, China is putting forward major projects of importance for the whole continent. If earlier, its economic initiatives were of regional importance only for East and South-East Asia, now China is putting forward global projects. They meet the interests of Kazakhstan, who realized at the beginning of independence the minuses of its continental position and is seeking out from it in the framework of the program «Nurly Jol». The interests of other countries – Russia, other post-Soviet countries, Europe, Turkey, and Iran – are considered from the point of view of Kazakhstan’s interests.